Snapshots in time: quantifying dynamics of coastal vessel traffic in a dolphin hotspot - William Carome; William Rayment; Elisabeth Slooten; M. Hamish Bowman; Emmanuelle Martinez; Stephen M. Dawson (New Zealand Journal of Marine and Freshwater Research, 2024)
Small vessels contribute substantially to coastal soundscapes, presenting myriad potential impacts on marine species and ecosystems, yet are challenging to monitor using standard tracking methods (e.g. AIS). Here, we present an automated camera system developed to quantify coastal vessel traffic in a core habitat for Hector's dolphins ( Cephalorhynchus hectori ) within Akaroa Harbour, Aotearoa New Zealand. Analysis of 55,569 images taken during the austral summer of 2019/20 showed that traffic was highest around midday, on weekends, and in January. A mean of 41.9 vessel trips per day transited the area of core habitat. Vessel speeds estimated from photographs were assigned to 5‐knot bins with 84% accuracy. Findings suggest vessel traffic in Akaroa Harbour has approximately doubled between 2006–2008 and 2020. Additionally, tours focused specifically on dolphins composed a significantly larger proportion of vessel traffic in 2020 than observed during 2006–2008. We validate the use of an automated camera system as a robust, novel, repeatable, and cost‐effective tool for quantifying fluctuations in coastal vessel traffic. Such tools can provide baseline data and help assess impacts, and their use can guide management action.

Estimating the abundance of the Hector's dolphins ( Cephalorhynchus hectori hectori ) that use Porpoise Bay, New Zealand - Max Harvey; Steve Dawson; William Rayment (New Zealand Journal of Marine and Freshwater Research, 2024)
Hector's dolphin, an endangered species endemic to the coastal waters of Aotearoa New Zealand, has a highly fragmented population structure. Low abundance of some local subpopulations, coupled with a stepping‐stone mode of gene flow, suggests that these are at high risk of extinction. During the austral summer, dolphins from the small, genetically distinct subpopulation found along the South Island's south‐east coast frequently use Porpoise Bay, an important foraging and calving area. The estimate of abundance of dolphins using the bay has not been updated since the introduction of protection measures in 2008 intended to mitigate bycatch in fisheries. Photo‐ID surveys, including random photography to estimate mark rate, were conducted during summer 2020. Using Chapman's version of the Lincoln‐Petersen estimator, it was estimated that 63 Hector's dolphins (95% CI = 46–79), including three new calves, used Porpoise Bay during the study period. While regression analyses showed no evidence of change since previous abundance estimates in 1996–97, 2002–03, and 2008, the very low estimated abundance validates fears for the long‐term persistence of this subpopulation. In this context, potential threats need to be managed within a precautionary framework, with a clear goal of facilitating recovery.

Multi‐decadal observations of the size structure of sperm whales at Kaikōura, New Zealand - Toby Dickson; William Rayment; Marta Guerra; Steve Dawson (New Zealand Journal of Marine and Freshwater Research, 2023)
Measurements of body length play an important role in the assessment of size and population structure of whales, allowing estimation of population parameters such as age at sexual and physical maturity. Uniquely, sperm whales can be measured from the interpulse interval (IPI) of their echolocation clicks, which contain information on the length of the head, which is allometrically related to body length. Measurements of IPI were taken from 424 acoustic recordings made between 1996 and 2019 at Kaikōura, New Zealand. Extrapolation to total length, using a new regression equation calculated from this population, revealed a significant increase in the mean length of whales visiting Kaikōura during summer in recent years (2014–2019), with no trend in the mean length for those visiting in winter. Increasing size during summer months appears to be driven by the growth of the same individuals returning summer after summer, combined with declining recruitment of new, smaller individuals. Thus, we hypothesise that the whales that visit in summer may represent an aging population. This is significant as sperm whales are a taonga [Of special significance to NZ Māori] species, top predators in the Kaikōura ecosystem, and the primary focus of the tourism industry at Kaikōura.

Estimated calving interval for the New Zealand southern right whale ( Eubalaena australis ) - Anthony Raphael Davidson; William Rayment; Steve M Dawson; Trudi Webster; Elisabeth Slooten (New Zealand Journal of Marine and Freshwater Research, 2018)
Southern right whales ( Eubalaena australis ) were widespread in New Zealand waters before commercial whaling in the nineteenth century caused drastic declines in their abundance and distribution. Following the cessation of whaling, the population has been recovering and is now slowly recolonising its former range. Estimates of population demographics, including reproductive output, are essential for predicting the trajectory of this population. We gathered photo‐identification data on female southern right whales during annual field trips to the Auckland Islands, the principal calving area in New Zealand waters. Forty‐five calving intervals were observed between 2006 and 2013 (mean interval = 3.31 years, 95% CI = 3.06–3.57). Incorporating the effects of possible missed calving events produced a plausible range of mean calving intervals from 3.17 to 3.31 years. Our results suggest that the calving interval of New Zealand southern right whales is similar to that found in populations elsewhere.

Observations of Hector's dolphins ( Cephalorhynchus hectori ) associating with inshore fishing trawlers at Banks Peninsula, New Zealand - William Rayment; Trudi Webster (New Zealand Journal of Marine and Freshwater Research, 2009)
Fishing activities have the potential to alter the behaviour of cetaceans and pose a threat through bycatch. We present observations concerning the influence of inshore trawling on group size and behaviour of Hector's dolphins ( Cephalorhynchus hectori ) at Banks Peninsula, New Zealand, made during photo‐ID surveys from 2003 to 2007. Aggregations of dolphins, typically involved in what we assumed to be foraging behaviour, were observed following small inshore trawlers year‐round. Group size was larger for aggregations of dolphins following trawlers (mean ± SE = 22.9 ± 1.3, n = 83) than for non‐trawler groups (3.7 ± 0.2, n = 439), and dolphins were typically in a more “excited” state, frequently exhibiting aerial and sexual behaviours. We suggest that trawlers increase the availability of prey for Hector's dolphins and hence foraging behind trawlers is an energetically favourable activity. However, following trawlers probably also increases the risk of being caught in trawl nets, compounding the threats faced by this endangered species.

Offshore distribution of Hector's dolphins at Banks Peninsula, New Zealand: Is the Banks Peninsula Marine Mammal sanctuary large enough? - Elisabeth Slooten; William Rayment; Steve Dawson (New Zealand Journal of Marine and Freshwater Research, 2006)
Aerial surveys of Hector's dolphins were carried out to evaluate the effectiveness of the Banks Peninsula Marine Mammal Sanctuary. In summer, the proportion of sightings inside the 4 nautical mile offshore boundary of the sanctuary was 79%. This dropped to just over 35% in winter. These estimates were used in a population viability analysis to determine whether the sanctuary needs to be extended to reduce dolphin bycatch to sustainable levels. We followed the standard procedure for setting limits on marine mammal bycatch in the United States to calculate a bycatch limit of 1.6 or 2.8 dolphins per year (depending on whether the sanctuary population is included). If the offshore boundary was extended to 15 nautical miles, the sanctuary would need to be extended alongshore north and south by more than 30 nautical miles to reduce bycatch to 2.8, or north and south by 60 nautical miles to reduce bycatch to 1.6 dolphins per year.